Jamaica. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Jamaica during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as family farming, field schools, greenhouses, protected agriculture, methodologies and cooperation between the public sector and private. Finally, work was done on the quarantine systems and on the value chains of vegetables, beans, sweet potatoes, bananas, yams and mangoes.